A comprehensive evaluation of the association between percent young and cross-national homicide rates - Rogers, Meghan L. (The British journal of criminology, 2017)
Is there an association between the proportion of the population that is young and national homicide rates, and when testing other theories cross-nationally is it necessary to control for this concept? To answer these questions, we carried out an extensive review of the empirical literature and then used data for the years 1999–2004 from a sample of 55 nations to test two predominant hypotheses: Percent young is significantly associated with homicide victimization rates across nations, and percent young accounts for a significant proportion of the overall variance in homicide victimization rates across nations. The results consistently indicated no significant association between percent young and homicide victimization rates across nations. Moreover, including percent young in models of cross-national homicide rates likely has negative ramifications for model fit. We situate these findings within the larger literature and provide a discussion of the implications for future cross-national homicide research.